Efficiency of Inflation Targeting in Transition Countries, the Case of the Czech Republic - Chytilová, Helena; Sedláček, Petr; Halás, Vladimír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2007)
This paper examines Czech experience with inflation targeting. It tries to assess empirically character of deviations from inflation targets throughout the time. It assess situation also in an international context. Consequently it analyse ability of IT regime to anchor inflation expectations in context of CNB’s forecasting performance. Results imply that although deviations were quite frequent in the Czech Republic, their occurrence has not been a barrier for delivering lower inflation and its lower volatility. Notwithstanding, its volatility remains significantly above the range experienced in the EU and the EMU countries. Regarding the inflation expectations, monetary policy surprises tend to be smaller over time,signalising that IT regime is priced by the markets. Thus, credibility of the CNB, concerning anchoring of inflation expectations, seems to improve after introduction of IT regime. It also indicates that IT regime is a quite appropriate regime for the upcoming period of time, which will be end up by the entry in the EMU
Vedoucí práce: Petr Sedláček
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2007
Rok obhajoby 2007
Keywords: národní hospodářství [obor dipl. práce]; diplomové práce; master's theses